La inscripción de Torrebaja, (Pueblo Nuevo del Guadiana, Badajoz) original modelo de la epigrafía cristiana - Ramírez Sádaba, José Luis (Antigüedad y Cristianismo, 1991)
The author analyses one tombstone discovered in the Visigoth cementery of Torrebaja in 1984 and now housed in the Museum of Badajoz. In the inscription (inventary number 11.604) the text stands out for its originality in various aspects.: 1) the struture- the personal data is given in the heading followed by the vida terrena y eterna in the principal part of the text, and ends with a moraiizing epilogue. 2) The vocabulary and its signification, which belongs to the more cultivated and poetical Christian tradition. The chronology oscilates between the last third of the Fourth Century and the first half of the Fifth Century. The name of the deceased, Pascencio, stands out due to the fact that it is inedited in the Peninsula Ibérica up to this moment.